Implicações psicossociais das cardiopatias na qualidade de vida de pessoas cirurgiadas e não-cirurgiadas - Moura, Tânia Regina Santos de (2008)
The main purpose of this study was to identify psychosocial factors related to heart diseases and their effects in the people s quality of life which were submitted to surgery intervention with heart risk. The specific purpose were: (I) to identify the participant s demographic profile submitted to heart-surgery proceeding which belongs to a group of risk; (II) to identify the factors of risk in people with heart disease and the psychological/physical/biological suffering in process of heart-surgery; (III) to study which are the psychosocial factors that lead emotional changes and their effects in the treatment evolution; (IV) to identify the meanings which people have about their quality of life; and (V) to analyse people s quality of life whose were submitted to heart-surgery interventions and people from the group of risk. The sample was compound by 91 male and female participants, everyone had heart disease and were submitted to surgery proceeding, all of them were from the group of risk. World Health Organization Quality Of Life-bref (WHOQOL), half-directed interviews and a demographic questionnaire were applied as instruments. Data collected by WHOQOL-BREF was processed based on the statistical package SPSS 15 and analyzed by descriptive statistic. Material collected by interviews was classified and analyzed, followed by Bardin´s Technical Analysis (2002). The results of the demographic questionnaire noticed that 52,7% of the participants were masculine and 47,3% were feminine, from this total 40% was in the 60-74 age bracket, the age with most risk, 23% between 30-40. The majority was married (68,1%), 42,9% had some kind of employment, about schooling 38,5% had the high school and 29,7%, school. The results of WHOQOL-brief demonstrated a cluster of 4 rules (physical, psychological, social relations and environment), with the most meaningful being the Rule III Social Relations (average 3,96), based in social support and sexual activities; and the Rule II Psychological (average 3,51). The results of the interviews showed that, in the thematic class heart disease, the biggest evidence was in the lifestyle category, in pre-heart disease (69%) and after-heart disease (31,0%). In the second class, heart-surgery proceeding, the most meaningful category was hospitalization, focusing the psychical-suffering (62,3%). In the third class, quality of life, the most important categories were: psycho-environmental (55,3%), related with health s care, feeding, habitation, job and leisure; psychosocial (21,1%), based on affection and self-esteem; and project of life (23,3%), associated to aspects of job, money, health and family. Hope the results of this research can help for a better understanding of heart diseases and quality of life and subsidies political health public programs.